(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article examines the organization of lessons in primary school based on the STEAM approach, its role in the educational process, and its significance in developing students’ competencies. The impact of interdisciplinary integration on the effectiveness of learning is thoroughly analyzed. Additionally, the pedagogical conditions for fostering practical, creative, and analytical skills in students through STEAM education are scientifically discussed.